Production of Sentential Negation in German and Italian Non-fluent Aphasia - Fyndanis, Valantis; Miceli, Gabriele; Capasso, Rita; Killmer, Helene; Malefaki, Sonia; Grohmann, Kleanthes K. (My University, 2023)
The ability of persons with non-fluent aphasia (PWAs) to produce sentential negation has been investigated in several languages, but only in small samples. Accounts of (morpho)syntactic impairment in PWAs have emphasized various factors, such as whether the negative marker blocks or interferes with verb movement, the position of the Negation Phrase in the syntactic hierarchy or the interpretability of negation. This study investigates the ability of German- and Italian-speaking PWAs to construct negative sentences, as well as the role of verbal working memory (WM) capacity and education in task performance and production of sentential negation. German and Italian differ in the syntactic properties of the negative markers that are relevant here (nicht and non, respectively). A sentence anagram task tapping into the construction of negative and affirmative declarative sentences was administered to 9 German- and 7 Italian-speaking PWAs, and to 14 German- and 11 Italian-speaking age- and education-matched healthy volunteers. We fitted generalized linear mixed-effects models to the datasets. There was no significant difference between negative and affirmative sentences in either group of PWAs. There was a main effect of verbal WM capacity on task performance, but no interaction between verbal WM capacity and production of negative vs. affirmative sentences. Education did not affect task performance. The results are discussed in light of different linguistically-informed accounts of (morpho)syntactic impairment in non-fluent aphasia.
Keywords: Education; German; Italian; Negation; Non-fluent aphasia; Polarity; entence anagram task; Verbal working memory